Field Equations in General Relativity with Internal Symmetry - Diep, Do Ngoc; Duc, Dao Vong; Tan, Ha Vinh; Viet, Nguyen Ai (Communications in Physics, 2012)
The covariant wedge products of tetrads in General Relativity are introduced and related field equations are derived. The electromagnetic dual field is treated in detail and it is shown that this field is closely related with one component field, which is eigenfunction of d’Alembertian operator. The formalism is developed to incorporate internal symmetry.